2011
DOI: 10.1007/s10570-011-9535-x
|View full text |Cite
|
Sign up to set email alerts
|

Water-soluble low-molecular-weight cellulose chains radially oriented on gold nanoparticles

Abstract: Cellulose chains bearing N-lipoyl group at the reducing-end as a sulfide linker, self-assembled on the surface of gold nanoparticles (CELL2Au, CELL13Au, and CELL41Au with the number average degrees of polymerization (DP n ) of 2, 13, and 41, respectively) were prepared. CELL2Au, CELL13Au, and CELL41Au were obtained via deprotection of the cellulose triacetate (CTA) self-assembled on the surface of gold nanoparticles that are consisting of CTA chains with corresponding DP n organized in a radial manner with hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…This method is known as the LbL (Layerby-Layer) technique [87] , and is widely applied not only to stabilize gold nanoparticle dispersions, but also to confer them with a desired surface charge, which is determined by the charge of the outmost polyelectrolyte layer [85]. Besides synthetic charged polymers, also bio-polymers [88] such as DNA [89 -93] , dextran [94] , cellulose [95,96] , chitosan [97,98] and various peptides and proteins can adsorb onto the nanoparticle surface, and have been widely used to make gold nanoparticles suitable for bio-applications. Moreover, polyelectrolyte multilayers can also serve as primers to make gold nanoparticles suitable for further surface modifi cations or coatings, such as silica [99] or pNIPAM microgels [100] .…”
Section: Physically Adsorbed Polymersmentioning
confidence: 99%
“…This method is known as the LbL (Layerby-Layer) technique [87] , and is widely applied not only to stabilize gold nanoparticle dispersions, but also to confer them with a desired surface charge, which is determined by the charge of the outmost polyelectrolyte layer [85]. Besides synthetic charged polymers, also bio-polymers [88] such as DNA [89 -93] , dextran [94] , cellulose [95,96] , chitosan [97,98] and various peptides and proteins can adsorb onto the nanoparticle surface, and have been widely used to make gold nanoparticles suitable for bio-applications. Moreover, polyelectrolyte multilayers can also serve as primers to make gold nanoparticles suitable for further surface modifi cations or coatings, such as silica [99] or pNIPAM microgels [100] .…”
Section: Physically Adsorbed Polymersmentioning
confidence: 99%
“…The layer of the blockwise alkylated tetrasaccharides (shell) and QDs (core) are included as the hydrodynamic diameter. We have reported water-soluble low molecular weight cellulose chains radially oriented on gold nanoparticles (Enomoto-Rogers et al 2011). In this previous article, we have described that hydrodynamic diameters of gold nanoparticles covered by cellulose chains include those of gold core and cellulosic shell, confirmed by transmission electron microscopic observation.…”
Section: Scheme 1 Synthesis Of Ethylated Cellobiose Derivativesmentioning
confidence: 61%
“…3−7 For example, Enomoto-Rogers et al found that cellulose with different degrees of polymerization (DP) selfassembled on the surface of gold nanoparticles exhibiting different dispersibilities in water. 3 Xie et al reported that the molecular weight of cellulose affected its entanglement, orientation, and crystallization, which had a great impact on the mechanical properties of the cellulose fiber. 4 Munster et al regulated the drug release process by changing the molecular weight of oxidized cellulose.…”
Section: Introductionmentioning
confidence: 99%
“…As the most abundant natural polymer, cellulose has been widely used in the fields of textile, food, biology, energy, and advanced materials. , The molecular weight of cellulose materials significantly affects their properties, such as solubility, mechanical properties, rheological properties, and crystallization behavior. For example, Enomoto-Rogers et al found that cellulose with different degrees of polymerization (DP) self-assembled on the surface of gold nanoparticles exhibiting different dispersibilities in water . Xie et al reported that the molecular weight of cellulose affected its entanglement, orientation, and crystallization, which had a great impact on the mechanical properties of the cellulose fiber .…”
Section: Introductionmentioning
confidence: 99%